Adult education as corporate social responsibility in Canadian mining companies: performing the good citizen for greater self-regulation. Issue 2 (4th March 2019) - Walker, Judith; Sarkodie, George
Abstract: This paper examines the underexplored role adult education activities play as part of Canadian Mining Companies' corporate social responsibility (CSR) efforts. We argue that adult education as CSR provides companies with a symbolic capital they can draw upon to detract from government oversight, increase profits, and continue operations. Taking place within a structure of increased corporate power and lacking any regulatory framework, CSR is often divorced from the overall ethos of a company. Moreover, the impact of adult educational initiatives on individuals and communities remains largely unknown, highlighting the need for further research.